Magnetite (Fe3O4) Nanoparticles in Biomedical Application: From Synthesis to Surface Functionalisation - Lokesh Srinath Ganapathe; Mohd Ambri Mohamed; Rozan Mohamad Yunus; Dilla Duryha Berhanuddin (Magnetochemistry, 2020)
Nanotechnology has gained much attention for its potential application in medical science. Iron oxide nanoparticles have demonstrated a promising effect in various biomedical applications. In particular, magnetite (Fe3O4) nanoparticles are widely applied due to their biocompatibility, high magnetic susceptibility, chemical stability, innocuousness, high saturation magnetisation, and inexpensiveness. Magnetite (Fe3O4) exhibits superparamagnetism as its size shrinks in the single-domain region to around 20 nm, which is an essential property for use in biomedical applications. In this review, the application of magnetite nanoparticles (MNPs) in the biomedical field based on different synthesis approaches and various surface functionalisation materials was discussed. Firstly, a brief introduction on the MNP properties, such as physical, thermal, magnetic, and optical properties, is provided. Considering that the surface chemistry of MNPs plays an important role in the practical implementation of in vitro and in vivo applications, this review then focuses on several predominant synthesis methods and variations in the synthesis parameters of MNPs. The encapsulation of MNPs with organic and inorganic materials is also discussed. Finally, the most common in vivo and in vitro applications in the biomedical world are elucidated. This review aims to deliver concise information to new researchers in this field, guide them in selecting appropriate synthesis techniques for MNPs, and to enhance the surface chemistry of MNPs for their interests.